The Role of Organizational Behavior Mediation in Organizational Cultural Relations and Education Quality: A Teacher's Perspective in Serang City Elementary School - Ida Dahlia; Sudadio Sudadio; Isti Rusdiyani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Improving the quality of education in elementary schools requires attention not only to academic inputs but also to internal organizational factors. This study investigates the mediating role of organizational behavior in the relationship between organizational culture and the quality of education in elementary schools in Serang City. A qualitative research design was employed to explore the perceptions and experiences of educators. Data were collected through in-depth interviews with 10 school principals and 20 teachers from various public elementary schools. Purposive sampling was used to ensure diverse perspectives based on school accreditation and performance levels. Thematic analysis was applied to identify patterns related to organizational culture, behavior, and education quality. The findings indicate that a strong, inclusive, and open organizational culture fosters positive organizational behavior among teachers, including higher motivation, collaboration, and job satisfaction. These behaviors, in turn, significantly contribute to the improvement of teaching practices and student achievement. Organizational behavior emerged as a key mediating variable that strengthens the influence of culture on education quality. The study highlights the critical role of school leadership in shaping a supportive organizational culture that promotes positive behavior and educational outcomes. Managing both culture and behavior effectively can create a more conducive learning environment and drive sustainable improvements in educational quality. The findings suggest that school principals should actively cultivate collaborative norms and teacher involvement in decision-making processes.